New legislation on the marketing and use of feed: status of nutritional supplements - Simona Sturzu,; Luminita Paraschiv (Medicamentul Veterinar)
The term "nutritional supplements" for animals is found first in the "Proposal for the European Parliament and of the Board amending Directive 93/74/EEC on feedingstuffs intended for particular nutritional purposes and amending Directives 74/63/EEC, 79/373/EEC and 82/471/EEC”, submitted by the European Commission to the European Parliament and Council Director for approval on July 28, 1997. The proposal was not approved, for the reasons that this category of "supplement animal nutrition” is already regulated at EU level onlegislation to feed, supplementary feed, feed premixes, food for particular nutritional purposes. In order to harmonize the conditions for the marketing and use of feed, to clarify of divergences anduncertainties due existing legislative vacuum, in order to ensure a high level of protection of public health and to provide adequate information to users and consumers, The Regulation (EC) No 767/2009 of the European Parliament and the Council on the marketing and use of feed, amending Regulation (EC) No 1831/2003 and repealing Council Directive 79/373/EEC, Council Directive 80/511/EEC, Directives 82/471/CEE, 83/228/EEC, 93/74/EEC, 93/113/EC and 96/25/EC and Commission Decision 2004/217/EC (1) aproved. The new regulation simplifies and clarifies the existing procedures and renewal the legislation for themarketing and use of feed materials, compound feed and bioproteine, including dietary feed.